น้ำหมักชีวภาพกระตุ้นการเจริญและเพิ่มความต้านทานโรคในกล้วยหอมทอง - อินทนนท์, เกวลิน; พวงจิก, ธัญพิสิษฐ์ (Thai Journal of Science and Technology, 2019)
Abstract The novel 2 formulas of the effective biofermented solutions, BM-1 and BM-2, were developed from 2 types of concentrated effective microorganism (EM) solutions (EM1 and EM2). Acid-base properties of the concentrated EM (EM1 and EM2) and the new formulas (BM-1 and BM-2) were evaluated. The BM-1 displayed higher pH value (pH 6) in comparison to that of EM1 while BM-2 showed the pH value similar to that of EM2 (pH 3.6-4.8). Types of microorganisms in both BM-1 and BM-2 were determined. Four groups of microorganisms, i.e. lactic acid bacteria, yeast, actinomycetes and fermenting fungi (as a major), were demonstrated in BM-1. For BM-2, it was also found the same 4 groups of microorganisms, together with photosynthetic bacteria as a major. Growth enhancement and disease resistance efficiency of the BM-1 and BM-2, were performed through Hom-Thong banana (Kluai Hom-Thong). Young offshoots with 1.5-meter height were cultivated and repeatedly nourished by BM-1 and BM-2 via root absorption once a week, for 6 months. Thereafter, leaves from each treatments were extracted and evaluated the amount of peroxide (PO) and polyphenol oxidase (PPO) by biochemical techniques. The results revealed that BM-2 increased the production of PO and PPO in the highest amount (p £ 0.05). In addition, BM-2 enhanced the height of the trunk but not the diameter in comparison to BM-1. Keywords: Kluai Hom-Thong; biofermented solution; effective microorganism; banana; disease tolerance